2021
DOI: 10.1016/j.jsurg.2020.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 on Surgical Training Across the United States: A National Survey of General Surgery Residents

Abstract: Introduction COVID-19 emerged as a global pandemic in 2020 and has affected millions of lives. Surgical training has also been significantly affected by this pandemic, but the exact effect remains unknown. We sought to perform a national survey of general surgery residents in the United States to assess the effect of COVID-19 on surgical resident training, education, and burnout. Methods An anonymous online survey was created and distributed to general surgery residents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
235
4
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(255 citation statements)
references
References 7 publications
9
235
4
7
Order By: Relevance
“…Considering the National Decree 718/2020 (extension on the graduation of the residents of the last year of the educational program) and the recommendation that the evaluations of cases and surgeries should be left in the hands of the professionals with more experience, the exposure of the residents in the operating room was limited, generating a reduction in surgical experience, mainly in residents of lower years (PGY – 1 and PGY – 2). These results are similar to other studies [ [16] , [17] , [18] , [19] ]. However, before the current global pandemic, surgical education has had to respond with new technologies, treatments and procedures to the dynamic changes in the knowledge of surgical disease, the demand in the supervision of resident doctors, and the demands for the patient safety [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Considering the National Decree 718/2020 (extension on the graduation of the residents of the last year of the educational program) and the recommendation that the evaluations of cases and surgeries should be left in the hands of the professionals with more experience, the exposure of the residents in the operating room was limited, generating a reduction in surgical experience, mainly in residents of lower years (PGY – 1 and PGY – 2). These results are similar to other studies [ [16] , [17] , [18] , [19] ]. However, before the current global pandemic, surgical education has had to respond with new technologies, treatments and procedures to the dynamic changes in the knowledge of surgical disease, the demand in the supervision of resident doctors, and the demands for the patient safety [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Another important discovery in this analysis was regarding the well-being and burnout of residents of surgical programs during the pandemic. The depletion rate was higher than the traditional rates reported in the literature [ 16 , 22 , 23 ]. A national survey of general surgery residents in the United States reported a burnout rate of 33.1% [ 16 ].…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In the United States, 106 urology trainees included in a cross-sectional survey also reported a decrease in surgical volume dependent upon the local prevalence of COVID-19 [ 13 ], with 76% of those working in a high COVID-19 area reporting decreased surgical volume compared to 22% in low COVID-19 area ( p = 0.01). Aziz et al reported a significant reduction in self-reported operative case volume amongst 1102 general surgery trainees in the United States [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Multiple survey studies were conducted evaluating resident and fellowship education during COVID-19. In general surgery, surveys of residents showed they received more didactic teaching during the pandemic than prior to the pandemic, as the majority (80.6%) went to completely online platforms 19 . In a survey of hematology and oncology fellows at a single institution, 100% of individuals appreciated the flexibility of online didactics, but only 63% felt that they learned the same amount online as in-person 20 .…”
Section: Discussionmentioning
confidence: 99%